New immunological aspects of peri-implantitis - Bárbara Bellocchio Bertoldo; Guilherme Oliveira Paulo; Taíssa Cássia de Souza Furtado; Thiago Lima Pereira; Virmondes Rodrigues Junior; Denise Bertulucci Rocha Rodrigues; Juliana Barbosa de Faria; Rodrigo César Rosa; Sanívia Aparecida de Lima Pereira (Einstein (São Paulo), 2024)
ABSTRACT Objective: This study aimed to compare the levels of HIF1-α, VEGF, TNF-α, and IL-10 in the peri-implant crevicular fluid of patients with and without peri-implantitis. Methods: Forty patients, comprising 16 with and 24 without peri-implantitis were selected. Results: Patients with peri-implantitis exhibited significantly higher HIF-1α levels than those without peri-implantitis (p=0.0005). TNF-α revealed significant positive correlations with IL-10 (p=0.0008) and VEGF (p=0.0246), whereas HIF-1α and IL-10 levels (p=0.0041) demonstrated a negative and significative correlation in the peri-implantitis group. Conclusion: This study, for the first time demonstrates the balance of HIF-1α, TNFα, IL-10, and VEGF in peri-implantitis. It shows an elevated HIF-1α levels in patients with peri-implantitis, which could have stemmed from persistent inflammation- triggered hypoxia. Furthermore, the positive correlation between TNF-α and VEGF suggests intensified proinflammatory activity in peri-implantitis. Nevertheless, further studies are essential to understand these immune dynamics in peri-implantitis.